Morphology and self-stress design of V-Expander tensegrity cells. (15th April 2017) - Fraddosio, Aguinaldo; Marzano, Salvatore; Pavone, Gaetano; Piccioni, Mario Daniele
Abstract: In this paper, we focus our attention on a class of tensegrity cells whose topology is based on the so-called "V-Expander" principle, and which can be easily assembled for constructing complex structures. In particular, we propose five new possible variants of the original "V-Expander" cell, characterized by an increasing complexity. After a topological study, as a starting point for the study of the mechanical properties of those cells as possible unit cells of lattice tensegrity materials, we perform a parametric analysis of the feasible self-stress states – i.e., self-stress states in auto-equilibrium and respecting the symmetry and the unilateral behavior of the elements (cables and struts) – as the geometry of the cell changes. This analysis allows us to discuss the features of the distribution of the self-stress in the elements for each one of the proposed V-Expander tensegrity cell variants.